Iran and Saudi Arabia relationship under Iran's pragmatic approach (1989-1993) - Amiri, Reza Ekhtiari; Ku Samsu, Ku Hasnita; Khorshidi, Majid; Piri, Daryoush (Marsland Press, 2011)
Iran’s revolution and its consequences distorted the previous close relationship between Iran and Saudi Arabia. This paper, first as introduction, will discuss the historical competition between ideological and pragmatic approaches in Iran’s foreign policy. Then it will study the domination of ideology in the foreign policy of Iran after the Islamic revolution and its role in Iran’s foreign relations with littoral states in the Persian Gulf region, in particular, Saudi Arabia. The study further examines the superiority of the pragmatic approach after the end of the Iran- Iraq war (1988) and gradual changes in Iran’s foreign policy from 1989. The research also analyzes the role of the new approach in re-establishing and improving the Iran-Saudi Arabia diplomatic relationship, which was severed in 1988, and limited cooperation of the two sides afterwards. The study concludes that despite Iranian-Saudi primary cooperation and agreement after the restoration of mutual ties, they were unable to maintain peaceful relations due to the bilateral and regional problems of the two countries.